EFEK MATERIAL CARBON TERHADAP SENSITIVE SENSOR CONTROL - Muhammad Yusuf Nurfani (Pusat Riset dan Inovasi Nasional, 2021)
Touchscreen is a technology used in the process of user selection access to control a function. In general, the touchscreen uses a cover that is used to cover the electrical function. The process of making cover control generally uses printing media with black INK material where in nature there are many chemical ingredients. In this study, an analysis of the nature of carbon will be carried out on the sensitivity of the control sensor in receiving a command. The results of the analysis found that the carbon material in INK affects the sensitivity quality of a sensor control function by 80% failure, so it is recommended for the forming agent of the base cover.